2017
DOI: 10.1075/dujal.6.1.07van
|View full text |Cite
|
Sign up to set email alerts
|

Syllable type development in toddlers acquiring Dutch

Abstract: Compiling syllable type inventories from children’s spontaneous speech is all but straightforward: so far studies vary considerably in their methodologies and consequently the selection of the speech samples differs. This paper shows that different methodologies for selecting a speech sample lead to substantial differences in syllable inventories. Two main sources for this variation are explored: differences in size and content of the speech samples. Both factors influence the results significantly and this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Van den Berg et al . (2017), Fikkert (1994) and Levelt et al . (2000) concluded that simple syllable types (CV, V and CVC) appear simultaneously and before complex syllable types.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Van den Berg et al . (2017), Fikkert (1994) and Levelt et al . (2000) concluded that simple syllable types (CV, V and CVC) appear simultaneously and before complex syllable types.…”
Section: Introductionmentioning
confidence: 99%
“…2000, Priester and Goorhuis‐Brouwer 2013; Stes 1977; Van den Berg et al . 2017). Dutch is a West‐Germanic language and the majority language in the Netherlands and parts of Belgium, as well as in Suriname, Aruba and the Dutch Antilles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations